Recent Progress on the Alloy‐Based Anode for Sodium‐Ion Batteries and Potassium‐Ion Batteries. Issue 9 (23rd September 2019) - Song, Keming; Liu, Chuntai; Mi, Liwei; Chou, Shulei; Chen, Weihua; Shen, Changyu
Abstract: High‐energy batteries with low cost are urgently needed in the field of large‐scale energy storage, such as grid systems and renewable energy sources. Sodium‐ion batteries (SIBs) and potassium‐ion batteries (PIBs) with alloy‐based anodes provide huge potential due to their earth abundance, high capacity, and suitable working potential, and are recognized as attractive alternatives for next‐generation batteries system. Although some important breakthroughs have been reported, more significant improvements are still required for long lifetime and high energy density. Herein, the latest progress for alloy‐based anodes for SIBs and PIBs is summarized, mainly including Sn, Sb, Ge, Bi, Si, P, and their oxides, sulfides, selenides, and phosphides. Specifically, the material designs for the desired Na + /K + storage performance, phase transform, ionic/electronic transport kinetics, and specific chemical interactions are discussed. Typical structural features and research strategies of alloy‐based anodes, which are used to facilitate processes in battery development for SIBs and PIBs, are also summarized. The perspective of future research of SIBs and PIBs is outlined. Abstract : Alloying‐based anodes have been intensively investigated in sodium‐ion batteries (SIBs) and potassium‐ion batteries (PIBs) as cost‐effective energy storage technologies. In this Review, the latest progress for alloy‐based anodes for SIBs and PIBs is summarized, mainly including Sn, Sb, Ge, Bi, Si, P, and their oxides, sulfides, selenides, and phosphides. The perspective of future research of SIBs and PIBs is outlined.